Association between breastfeeding, obstetric and perinatal factors with the child neuropsychomotor development (Research, Society and Development, 2021)
The objective of this study was to evaluate the association between breastfeeding, obstetric and perinal factors with child neuropsychomotor development. The study was a descriptive, exploratory and quantitative field research, which aimed to analyze the association between breastfeeding, obstetric and perinatal factors with child neuropsychomotor development (DPNP). The sample consisted of 52 mothers who had children aged 6 to 12 months old and who were undergoing procedures at the basic health unit, in the city of Patos, Paraiba. Data collection was applied with the application of a semi-structured questionnaire, in which the DPNP, delivery data, obstetric factors, breastfeeding data and association with the DPNP data were evaluated. The results show that the majority of the children who were part of the sample have dnpm compatible with age, the longer breastfed the more in accordance with the appropriate development. The study also showed that mothers who had trauma during pregnancy and children born below gestational age had DPNP not compatible with age. It was possible to verify the benefits brought by the practice of exclusive breastfeeding and its positive performance in child development, as well as it was possible to discuss the gestational factors that are associated in the DPNP of these children.